Use of Natural Diatoms doped with gold nanoparticles for Gentamicin Drug Delivery - Chavez Chico, Eva Anai (2020)
Diatoms are unicellular photosynthetic algae covered with siliceous cell wall, with a remarkably interesting ordered porous structure with different levels of hierarchical porosity from nano to macropores. They have a very spectacular and diverse nano and macrostruture cellwalls that impart different architecture to their structure. The compatibility of siliceous matrix has been proved in other systems. Therefore, due to the ordered pore structure, the high surface area, biocompatibility, availability, and low processing cost, they can have a great potential for drug delivery compared with other silica systems used for this application that required much more difficult synthesis processes and used of expensive reactants. Natural and cultured Diatoms contain various therapeutic compounds such as proteins and complex polysaccharides which can be used in various therapeutic applications. It has been found that the marine diatoms contain polyunsaturated fatty acids and bioactive compounds with potential antioxidant and anticancer properties. Therefore, in the present work it is proposed to explore the use of a natural diatom (Aulacoseria ) from the Guayllabamba region of Ecuador doped with gold nanoparticles as potential drug delivery systems. The diatoms are characterized by Ultraviolet-Visible Spectroscopy, X-ray Powder Diffraction (XRD), Scanning Electron Microscopy (SEM), Fluorescence Microscopy, Raman, and Surface area (BET). The samples were dealuminated and functionalized with gold nanoparticles and the controlled delivery was studied using Gentamicin as model drug.